خدمة اللغة العربية لعلوم الشريعة الإسلامية - علم أصول الفقه نموذجًا - حذيق, العيد (University of Eloued جامعة الوادي, 2020)
هذه الورقةُ البحثيَّة بعنوان: خدمة اللُّغة العربيَّةِ لعلوم الشَّريعة الإسلاميَّة - علم أصول الفقه نموذجًا -، وهي تُعالجُ إشكالَ: كيف كانت اللُّغة العربيَّة خادمةً لعلوم الشَّريعة الإسلاميَّة؟وللإجابة عن هذا الإشكال؛ فقد اخترتُ علمًا من العلوم الإسلاميَّة؛ هو علمُ أصول الفقه، وحاولت أن أكشف عن معالم خدمة اللُّغة العربيَّة له، من خلال الخُطّة الآتية: مقدمةٍ وثلاثةِ مقاصد وخاتمة. أمَّا المُقدِّمة؛ فقد مهَّدت فيها بوثاقة العلاقة بين علوم اللغة وعلوم الشريعة منذ القِدَم. وأمَّا المقصدُ الأوَّل: حاجة علم أصول الفقه إلى اللُّغة العربيَّة ووجهها؛ فقد بيَّنت فيه أنَّ اللُّغة العربيَّة أحدُ الروافد الثلاثة التي استمد منها أصول الفقه مسائله ومباحثه، وأنَّ وجه الحاجة إلى العربية كون النصوص المُشتَغلِ عليها (الكتاب والسنة) باللغة العربية. ولمَّا كانت القضايا الأصوليَّة الَّتي مدركُها لغويٌّ كثيرةً، وحصرها عسيرٌ؛ فقد اخترتُ نموذجين، وجعلتهما في مقصدين. أمَّا المقصد الثَّاني: نموذجٌ من باب الدلالات (مفهوم المخالفة)؛ فهو المثال الأول، وأمَّا المقصد الثَّالث: نموذجٌ من باب القياس (قاعدة تعليق المشتق)؛ فهو المثال الآخر. ثمَّ ختمتُ بما توصَّلتُ إليه من نتائج. هذا ومن أهمِّ ما توصَّلتُ إليه في هذا البحث: أنَّ علوم اللُّغة العربيَّة كانت واحدا من الروافد الثلاثة التي استمد منها أصول الفقه، وأنَّ الأصوليين استثمروا في مسائل اللغة العربيَّة فحوَّلُوا جُزءًا منها من مُجرَّد ضوابط للملكات اللّسانيَّة، إلى قواعد كليَّة يُستعان بها في استنباطِ الأحكام الشَّرعيَّة من أدلَّتها التَّفصيليَّة. This research paper is entitled "The Arabic Language Service to the Sharia Sciences : The Science of the Principles of Islamic Jurisprudence as a Model", and it addresses the question of : How was the Arabic Language a servant to Sharia sciences? To answer the question in hand , I chose –amongst Islamic sciences- the science of the principles of jurisprudence , and I tried to reveal the Arabic service to it through a plan of an introduction, three chapters and a conclusion. In the introduction, I paved the way to the study by showing the close relationship between linguistics and Sharia sciences since ancient times. The first chapter entitled "The Science of the Principles of Jurisprudence Need for the Arabic Language and its Aspects" tackles the Arabic language as one of the three tributaries from which the science of the principles of jurisprudence draws its issues, questions and subjects ; and that this need lies in the fact that the studied texts (the Holy Quran and Sunnah) are written in Arabic. And since there is a myriad of fundamentalist issues that are linguistic in nature, I have chosen two models with each treated in a chapter. The second chapter entitled "A Semantic Model (the Concept of Differentiation) is the first example; whereas the third chapter entitled "An Analogous Model (the Rule of Suspending the Derivative) is the second one. Then, I concluded with the acquired findings. The most important findings of this research include : o Firstly, the Arabic language is one of three tributaries from which the science of the principle of jurisprudence draws its questions and issues. o Secondly, the fundamentalists have invested in matters of the Arabic language ,and they have converted part of them from mere linguistic regulations to macro rules useful in deriving Sharia judgments from their detailed evidence.
ملتقى:تنزيل النص الشرعي على الواقع في ضوء العلوم الإنسانية والاجتماعية كلية العلوم الإنسانية والعلوم الإسلامية والحضارة / قسم العلوم الإسلامية 11 مارس 2020 جامعة عمار ثليجي، الأغواط
Keywords: اللغة العربية، علوم الشريعة، علم أصول الفقه; Arabic Language Sharia Sciences ; The Science of the Principles of Islamic Jurisprudence